1994
DOI: 10.18174/njas.v42i1.613
|View full text |Cite
|
Sign up to set email alerts
|

Physiological determinants to optimize metabolic utilization of dietary amino acids for animal protein production

Abstract: Dietary amino acids are distributed between different metabolic pathways depending on availability, physiological priority and metabolic capacity. Metabolic utilization of dietary amino acids for animal protein production can be optimized by making proper use of physiological determinants. This entails the development of so-called 'physiological feeding strategies'. An overview of recent achievements is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…(1997). S CHREURS et al. (1994) estimated the conversion efficiency of amino acids from whole‐egg to 1‐day‐old‐chick and found that tryptophan was utilized considerably less than any other amino acid.…”
Section: Discussionmentioning
confidence: 99%
“…(1997). S CHREURS et al. (1994) estimated the conversion efficiency of amino acids from whole‐egg to 1‐day‐old‐chick and found that tryptophan was utilized considerably less than any other amino acid.…”
Section: Discussionmentioning
confidence: 99%